Influence of personal resources on career adaptability among undergraduate students in a public university in Malaysia - Khoo, Kai Le (2019)
Industry is expecting a “finished product” who able to display a well-rounded skills to adapt to constant changes. However, many graduates are struggling with the shift from school. This thesis is aimed at examining the influence of personal resources on career adaptability in terms of concern, control, curiosity and confidence among university undergraduates. Based on the reviewed literature, three possible predictors of career adaptability are identified for further investigation, namely emotional intelligence, self-esteem and career self-efficacy. Correlation research design was used in this study. A set of self-reported structured questionnaire was deployed for data collection through direct administration of the instrument among the final year undergraduates’ students (n=205). The results were analyzed using descriptive statistics and inferential statistics based on the study’s research questions and research hypothesis. The findings indicated that there was a significant correlation between emotional intelligence, self-esteem, career self-efficacy, and career adaptability among undergraduates. The findings also showed that emotional intelligence, selfesteem and career self-efficacy among final year undergraduates in public university are important predictors of career adaptability. The most significant predictor in this study on career adaptability was career self-efficacy. The results of this study would assist stakeholders in the development of undergraduates’ personal resources to improve undergraduates’ career adaptability.